Myeloid-Derived Suppressor Cells: The Expanding World of Helminth Modulation of the Immune System - Stevenson, Mary M.; Valanparambil, Rajesh M.; Tam, Mifong (Frontiers in Immunology, 2022)
Infection with helminths or parasitic worms are highly prevalent worldwide especially in developing regions. Helminths cause chronic infections that are associated with suppression of immune responses to unrelated pathogens, vaccines, and by-stander antigens responsible for dysregulated immune responses as occurs in diseases such as allergies. Helminths use multiple mechanisms to modulate the immune system to evade the highly polarized type 2 immune response required to expel adult worms and for immunity to reinfection. Anthelmintic drugs are efficient in reducing adult worm burdens in helminth-infected individuals, but resistance to these drugs is rapidly increasing and vaccines against these pathogens are not available. Emerging evidence indicate that helminths induce myeloid-derived suppressor cells (MDSC), originally described in tumor-bearing mice and cancer patients. MDSC are a heterogenous population of immature cells that consist of two distinct sub-populations, polymorphonuclear (PMN)-MDSC and monocytic (M)-MDSC based on morphology and phenotype. MDSC suppress the function of T cells and other innate and adaptive immune cells including NK cells and B cells. During cancer or infection with bacteria or viruses, there is marked expansion of MDSC. Furthermore, the frequencies of MDSC correlate inversely with the prognosis and survival of tumor-bearing hosts as well as bacterial and viral burdens, persistence, and outcome in infected hosts. Currently, there is a paucity of data on MDSC and helminth infections. Here, we provide a survey of the evidence accumulated so far that overall support a role for MDSC in modulating immune responses during helminth infections. We review data from studies in various helminths, including those that infect humans. Finally, we summarize the progress to date in understanding the role of MDSC in helminth infections and briefly discuss potential host-directed strategies to target MDSC-mediated suppression of immune responses to helminths in favor of development of immunity to eliminate adult worms and possibly induce protection against reinfection.